Strategi Hedging Indonesia dalam Kerja Sama Infrastruktur dengan Tiongkok Melalui Belt and Road Initiative (BRI) - Ferdian Nando Simanullang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
China’s Belt and Road Initiative (BRI) has intensified infrastructure cooperation with developing countries, including Indonesia. While the initiative provides opportunities for infrastructure development, investment inflows, and technological advancement, it also raises concerns regarding asymmetric dependence and strategic autonomy. This study aims to analyze Indonesia’s hedging strategy in infrastructure cooperation with China under the BRI framework and to explain the economic benefits derived from its implementation. The research employs a descriptive qualitative method using literature studies and documentation as data collection techniques. The analytical framework is based on Cheng-Chwee Kuik’s hedging theory, particularly the concepts of Returns-Maximizing Options and Risk-Contingency Options. The findings indicate that Indonesia adopts a dual-track strategy by simultaneously maximizing economic gains and mitigating potential risks. Through economic pragmatism, Indonesia utilizes Chinese investment and technology to accelerate infrastructure development. At the same time, the government applies binding-engagement measures such as domestic content requirements and limits on state guarantees, while maintaining majority ownership in strategic projects. Indonesia also diversifies economic partnerships, promotes downstream industrialization, rejects external political dominance, and strengthens security cooperation with other major powers. The study concludes that Indonesia’s hedging strategy enables the country to obtain substantial economic benefits, including improved connectivity, industrial transformation, and energy security, while preserving fiscal sovereignty and strategic autonomy.